Treatment burden and associated factors: a population-based survey in Central Denmark Region 2017: Marie Hauge Pedersen. (25th October 2022) - Pedersen, MH; Duncan, P; Lasgaard, M; Friis, K; Salisbury, C; Larsen, FB
Abstract: Background: Exploring treatment burden at a population level can provide evidence of the types of patients who need special attention and support. We aimed to determine factors associated with high perceived treatment burden in a population-based survey of adults living in the Central Denmark Region (23% of the Danish population). Methods: The Danish Multimorbidity Treatment Burden Questionnaire (MTBQ) was included in the 2017 Danish population health survey. 28, 627 individuals aged 25 years or over participated (64% response rate). Individuals who reported having one or more medical conditions or attending regular health check-ups were asked to complete the MTBQ. A global MTBQ score was calculated (range 0-100) and both the continuous scores and a four-category grouping of the scores into no, low, medium and high burden were used to statistically assess the association between treatment burden and sociodemographic and health-related factors. Results: 13, 407 individuals completed the Danish MTBQ (mean age 59 years). Treatment burden was negatively associated with self-related health (rs = -0.45, P < 0.0001), health-related quality of life (rs = -0.46/-0.51, P < 0.0001) and positively associated with the number of long-term conditions (rs = 0.26, P < 0.0001) and perceived stress (rs = 0.44, P < 0.0001). Higher treatment burden was associated with young age, male sex, high educational level, unemployment, not living with a spouse/cohabitant, living with child(ren) and specific long-term conditions, including heart disease, stroke, diabetes and mental illness. Conclusions: This is the first known population-based study of treatment burden. The findings provide important evidence to policy makers and clinicians about sociodemographic groups at risk of higher treatment burden. We recommend that patient-perceived treatment burden is included when evaluating interventions targeting patients with long-term conditions and multimorbidity and health-care system reorganisations. Key messages:  Treatment burden is associated with poor health and health-related quality of life and, among others, young age, male sex, unemployment, not living with a spouse, and specific long-term conditions.  We recommend that patient-perceived treatment burden is included when evaluating interventions targeting patients with long-term conditions and multimorbidity and health-care system reorganisations.